A origem dos conceitos de “bom e mau”, “bom e ruim” em Nietzsche - Santos, Carina de Paula (2022)
The objective of this dissertation is to analyze the importance of the question of the value of values for the construction of the critique of morality present in the first dissertation of the Genealogy of Morals, and consequently to understand how such a project enables the development of a new positive dimension in Nietzsche's thought. In this way, we analyze how the philosopher exposes the immanent origin of values and later develops the genealogical procedure that allows the examination of the conditions under which values were created and modified throughout history. From this, we investigate the distinctions between noble morality and slave morality and how these two types proceed to engender valuations - the first as an expression of a powerful and affirming physiology, and the second as a reflection of a weak and impotent constitution. We will show that the values that govern western civilization characterize the worldview of the man of resentment, who, led by the spirit of revenge of the priestly caste, managed to universalize his weakness and make a morality that denies the world of life triumph. Finally, we will try to understand how Nietzsche articulates the concepts of life and value, which will give us the key to glimpse the propositional perspective of his critique of morality.